Reconstruction Management for Neglected Tripod Fracture with Ophthalmic Injuries: A Case report: Poster Presentation - Case Report - Resident - Priscillia Tondolambung; Vera Sumual; Victor Pamolango; Freili Akay (Majalah Oftalmologi Indonesia, 2023)
Introduction : Tripod fracture or zygomatico-maxillary complex fracture are among the most common injuries to facial structures, which can make reconstruction more difficult. This case highlights the reconstruction of neglected tripod fracture. Case Illustration : A 17-year-old male was presented with enophthalmos in his right eye. He had an accident three months prior and had received head surgery. After that, the patient came back with a pan-facial fracture. VA on RE was 1/300, limited movement upwards, 4 mm lagophthalmos, negative Bell’s phenomenon, infiltrates and cicatrices on the cornea. CT-scan examination showed tripod fractures. The surgery was performed by the reconstruction division with an oral and maxillofacial surgeon. Nineteen days after surgery, there has been some improvement in the orbital misalignment. Discussion : Delayed intervention in this case, increased the difficulty of surgical treatment and could lower the success rate of surgery. If the indication is obvious, an immediate intervention will give better results because soft tissue scarring is minimized and fractures are easily reduced. During the procedure, we released the orbital muscle entrapment and repaired the deviated bone and callus with an osteotome to achieve mobility. Therefore, the tripod fracture was fixed with three-point fixation, followed by reconstruction of the maxilla and mandible. The result after surgery showed some improvements in aesthetics but not in vision. Conclusion : Orbital reconstruction with mini-plate implants in three-point fixation as the management of orbital fractures is effective, but its accuracy is difficult to assess during surgery, especially when coupled with delayed intervention cases. Early reconstruction is recommended for a better cosmetic result.